Using automated methods to detect safety problems with health information technology: a scoping review. (14th November 2022) - Surian, Didi; Wang, Ying; Coiera, Enrico; Magrabi, Farah
Abstract: Objective: To summarize the research literature evaluating automated methods for early detection of safety problems with health information technology (HIT). Materials and Methods: We searched bibliographic databases including MEDLINE, ACM Digital, Embase, CINAHL Complete, PsycINFO, and Web of Science from January 2010 to June 2021 for studies evaluating the performance of automated methods to detect HIT problems. HIT problems were reviewed using an existing classification for safety concerns. Automated methods were categorized into rule-based, statistical, and machine learning methods, and their performance in detecting HIT problems was assessed. The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta Analyses extension for Scoping Reviews statement. Results: Of the 45 studies identified, the majority ( n  = 27, 60%) focused on detecting use errors involving electronic health records and order entry systems. Machine learning ( n  = 22) and statistical modeling ( n  = 17) were the most common methods. Unsupervised learning was used to detect use errors in laboratory test results, prescriptions, and patient records while supervised learning was used to detect technical errors arising from hardware or software issues. Statistical modeling was used to detect use errors, unauthorized access, and clinical decision support system malfunctions while rule-based methods primarily focused on use errors. Conclusions: A wide variety of rule-based, statistical, and machine learning methods have been applied to automate the detection of safety problems with HIT. Many opportunities remain to systematically study their application and effectiveness in real-world settings.